GAP Analysis Penerapan Standar Pedoman Budidaya Sapi Potong (Peraturan Menteri Pertanian Nomor 46 Tahun 2015) di Kota Tanjungpinang - Eko Sutrisno; Rina Febrinova Rina Febrinova; Kusmiati Kusmiati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The need for protein can be seen from the high demand for beef in Tanjungpinang City. However, beef production in Tanjungpinang City has not increased proportionally. As a result, Tanjungpinang City still has to rely on beef from outside the region because beef cattle cultivation has not yet reached an optimal level. This research aims to analyze the GAP for the technical implementation of beef cattle fattening business following the Standard Cultivation Guidelines (SPB) recommended by the Ministry of Agriculture through Minister of Agriculture Regulation Number 46/Permentan/PK.210/8/2015 concerning Guidelines for Good Beef Cattle Cultivation. This research was conducted in Tanjungpinang City and involved breeders who were members of 15 livestock groups and 195 breeders. This research was conducted through a survey using purposive sampling. The population of this study consisted of breeders who had kept five or more cows in a pen and had been cultivating livestock for the last five years. Based on these criteria, the research sample consisted of 44 breeders. The results of the research are the technical implementation of beef cattle fattening cultivation in Tanjungpinang City based on the Standard Cultivation Guidelines (SPB) recommended by the Ministry of Agriculture through Minister of Agriculture Regulation Number 46/Permentan/PK.210/8/2015 concerning Guidelines for Good Beef Cattle Cultivation. The research results show that environmental condition indicators have a GAP Analysis percentage of 57 percent, livestock seeds 33 percent, building conditions 56 percent, feed availability 51 percent, and livestock facilities and animal health 40 percent. The highest percentage of GAP Analysis is the condition of the building, while the lowest percentage is the selection of livestock seeds.